Android Mobile Application System for Pet Care Services Using MVVM Architecture - Sari, Putri Intan; Nashirin, Khairun; Arifudin, Muhammad; Setiawan, Yanto (International Journal Labs, 2023)
The K1 clinic (Kawan Kewan) is a veterinary clinic in the city of Magelang that was established in 2018. There are many ways to improve the services at the K1 clinic (Kawan Kewan). Pet Owners are worried when going to the vet clinic because they are uninformed of the incurred expenses that they will get after having a medical examination at the clinic. Meanwhile the clinic needs a system that can manage administration and can increase the satisfaction of customers who come to the clinic, as well as manage all administration related to the veterinary service process. The primary goal of this research is to make an Android-based mobile application to simplify administration and give a better experience for every customer who come to the veterinary clinic. In this research, the waterfall method is used as a testing tool because this method allows for departmentalization and control. Therefore, this method is suitable for solving the existing cases at the K1 Veterinary Clinic (Kawan Kewan) by utilizing the MVVM architecture framework for Android application development. The application, which was created utilizing the MVVM design and the Kotlin programming language, was tested on users and produced pleasing results. It efficiently meets the needs of users and clinics, making pet services possible.